2012 SC Companion: High Performance Computing, Networking Storage and Analysis 2012
DOI: 10.1109/sc.companion.2012.109
|View full text |Cite
|
Sign up to set email alerts
|

A Highly-Accurate and Low-Overhead Prediction Model for Transfer Throughput Optimization

Abstract: An important bottleneck for data-intensive scalable computing systems is efficient utilization of the network links that connect the collaborating institutions with their remote partners, data sources, and computational sites. To alleviate this bottleneck, we propose an application-layer throughput optimization model based on parallel stream number prediction. This new model extends our two previous models (Partial C-order and Full Second-order) to achieve higher accuracy and lower overhead predictions. Our ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…In future work, the author can add more experiments to extend the historical database, based on different parameters such as RTT and bandwidth. Also, the author can combine the prediction model and the previous model [2] to provide a better solution finding optimal PCP values in the real network environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work, the author can add more experiments to extend the historical database, based on different parameters such as RTT and bandwidth. Also, the author can combine the prediction model and the previous model [2] to provide a better solution finding optimal PCP values in the real network environments.…”
Section: Resultsmentioning
confidence: 99%
“…However, setting the optimal numbers for these parameters is a challenging problem, since poorly tuned parameters can cause underutilization of the network or they can overburden the network and degrade the performance due to increased packet loss, endsystem overhead, and other factors. In addition, the author's previous work [1], [2] sought to find a solution for an efficient big data transfer by utilizing the well-known protocol GridFTP with PCP (Pipelining-Concurrency-Parallelism). In this paper, the author proposes a prediction model based on historical data to find optimal values for pipelining, concurrency and parallelism and reports very promising experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…There has been several efforts in Kasparan et al [17] analyzed how pipelining affects throughput in local area networks and high-speed downlink packet access networks. Kim et al [19] and Yildirim et al [32] considered the combined effect of parallelism, pipelining, and concurrency on end-toend data transfer throughput. Natarajan et al [28] showed that using a single stream for transferring independent web objects is very inefficient in high latency networks.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work [18], we proposed network-aware transfer optimization by automatically detecting bottlenecks and improving throughput via utilization of network and end-system parallelism. We developed three highly-accurate models [19,20,21] which would require as few as three sampling points to provide accurate predictions for the optimal parallel stream number. These models have proved to be more accurate than existing similar models [22,12] which lack in predicting the parallel stream number that gives the peak throughput.…”
Section: Related Workmentioning
confidence: 99%
“…However, setting the optimal levels for these parameters is a challenging problem, and poorly-tuned parameters can either cause underutilization of the network or overburden the network and degrade the performance due to increased packet loss, end-system overhead, and other factors. Among these parameters, pipelining specifically targets the problem of transferring a large numbers of small files [13,14,28]. In most control channelbased transfer protocols, an entire transfer must complete and be acknowledged before the next transfer command is sent by the client.…”
Section: Dynamic Protocol Tuning Algorithmsmentioning
confidence: 99%